2005
DOI: 10.1038/sj.onc.1208743
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 stimulates the membrane recruitment of p120GAP to modulate Ras and Raf-1 activity

Abstract: Annexin A6 is a calcium-dependent membrane-binding protein that interacts with signalling proteins, including the GTPase-activating protein p120GAP, one of the most important inactivators of Ras. Since we have demonstrated that annexin A6 inhibits EGF-and TPA-induced Ras signalling, we investigated whether modulation of Ras activity by annexin A6 was mediated via altered subcellular localization of p120GAP. First, we exploited our observation that high-density lipoproteins (HDL) can activate the Ras/MAP kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(149 citation statements)
references
References 53 publications
9
140
0
Order By: Relevance
“…Importantly, similar results were obtained when anti-SNAP23 or anti–syntaxin-4 staining was compared in A431 wild-type (A431wt) cells, which lack endogenous AnxA6 (Smythe et al , 1994; Grewal et al , 2005), and the stable AnxA6-expressing A431-A6 cell line (Figure S3, A and B). In contrast, stable AnxA6 knockdown HeLa cells (HeLa-A6-KD) showed increased SNAP23 and syntaxin-4 PM localization (Figure S3C).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Importantly, similar results were obtained when anti-SNAP23 or anti–syntaxin-4 staining was compared in A431 wild-type (A431wt) cells, which lack endogenous AnxA6 (Smythe et al , 1994; Grewal et al , 2005), and the stable AnxA6-expressing A431-A6 cell line (Figure S3, A and B). In contrast, stable AnxA6 knockdown HeLa cells (HeLa-A6-KD) showed increased SNAP23 and syntaxin-4 PM localization (Figure S3C).…”
Section: Resultssupporting
confidence: 71%
“…Therefore we initially compared the localization of SNAP23 and syntaxin-4 in CHO wild-type (CHOwt) and the well-characterized CHO-A6 cell line (Grewal et al , 2000, 2005; Pons et al , 2001; Rentero et al , 2006; Cubells et al , 2007, 2008). CHOwt cells express low amounts of AnxA6, whereas AnxA6 levels in CHO-A6 cells are similar to AnxA6 expression levels observed in other commonly used cell lines, such as HeLa and NRK (Cubells et al , 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Moreover, we recently demonstrated that p120GAP-mediated inactivation of epidermal growth factor receptor (EGFR)-induced Ras/MAPK signaling is facilitated by annexin A6 (AnxA6), a member of the annexin protein family. 30,38 Loss of AnxA6 in EGFR-overexpressing and estrogen receptor (ER)-negative breast cancer cells (BCCs) is associated with elevated Ras, Raf, and MAPK activity, and vice versa, upregulation of AnxA6 strongly reduces cell growth of EGFRoverexpressing BCCs. 39,40 Taken together, the potential tumorsuppressive function of each GAP is associated with elevated Ras activity but seems to be restricted to certain cell types, and it is tempting to speculate that specific GAPs control Ras activity in different tissues, but their inhibition is a general mechanism to provoke oncogenic activity and carcinogenesis via elevated wild-type Ras activity.…”
Section: Functional Differences Of Ras Isoforms and Differential Gap mentioning
confidence: 99%
“…HDL binding to receptors such as SR-BI 6 activates various cellular processes, including endothelial nitric-oxide synthase activation in endothelial cells (1)(2)(3) and proliferation in smooth muscle cells (4) but also cell surface localization of SR-BI in hepatocytes (5). Downstream targets of HDL include Src family kinases, phospholipase C and D, Ras, phosphatidylinositol 3-kinase (PI3K), Akt, the mitogen-activated protein kinase (MAPK) pathway (Mek1/2 and Erk1/2), and Rac/Rho GTPases (1)(2)(3)(4)(5)(6)(7)(8). Other kinases implicated in HDL-or apoAI-inducible cholesterol transport include protein kinase C (PKC), protein kinase A (PKA), c-Jun N-terminal kinase (JNK), and p38 MAPK (9 -14).…”
mentioning
confidence: 99%